WO(MEN) IN INDIAN FICTION - Savitha, S.; Rema, V.; Nagamani, K. (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to portray the subjugation of women in family and society and the impact of the emerging trends of feminist perspectives on the portrayal of womanhood in literature. Since generations, woman had held a celebrated position closer to deities; though in reality they held a very dependent status stigmatized only to do the household chores and responsible for the reproductive function. The prevalent practices of ‘sati’, ‘purdah’ speak volumes of subjugation of women for countless centuries. The women writers’ attempt to voice forth the problems of the so far muted gender poses a big challenge because of the unconscious deliberation of subjugation that had been so deeply embedded in the social framework.